2013
DOI: 10.1159/000350930
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Reaction to Golimumab: Tumor Necrosis Factor α Inhibitor Inducing Psoriasis Pustulosa

Abstract: Importance: Golimumab is a human monoclonal antibody, used for rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis. Adverse reactions are increasing with this class of medication (tumor necrosis factor α inhibitors). Observations: The authors present a case of a female patient who presented with psoriasis pustulosa after the use of golimumab for rheumatoid arthritis. Conclusions and Relevance: Paradoxically, in this case, golimumab, which is used for psoriasis, induced the pustular form of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, the mean time for the onset of symptoms has not been established, as the time interval in cases varies significantly. Lesions resolved after discontinuation of therapy in all patients and remained stable while treatment continued 6 . Harrison MJ, Dixon WG, Watson KD, King Y, Groves R, and Hyrich KL conducted a study in RA patients who received anti-TNF therapy to identify those who developed psoriasis and identified 41 cases.…”
Section: Case Reportmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the mean time for the onset of symptoms has not been established, as the time interval in cases varies significantly. Lesions resolved after discontinuation of therapy in all patients and remained stable while treatment continued 6 . Harrison MJ, Dixon WG, Watson KD, King Y, Groves R, and Hyrich KL conducted a study in RA patients who received anti-TNF therapy to identify those who developed psoriasis and identified 41 cases.…”
Section: Case Reportmentioning
confidence: 87%
“…Skin lesions such as eczema, drug eruptions, drug-induced systemic lupus, dermatomyositis, lymphomatoid papulosis-like rash and psoriasis were reported in 10% of patients who received anti-TNF therapy. Paradoxical psoriasis has an annual incidence of 5% 5,6 . Studies have shown that smoking is the main risk factor for the development of lesions 5 .…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsies showing acanthosis, spongiform pustules, papillary dermal edema and telangiectasias were also described in patients on golimumab who presented with a widespread pustular eruption, and had the picture of pustular psoriasis on histopathology. 6 Psoriasiform features were also noted on scalp biopsies from patients on infliximab and adalimumab. Patients presented with scaly patches of alopecia.…”
Section: Psoriasiform Patternmentioning
confidence: 92%